A 17-Year-Old Female with Systemic Lupus Presents with Complex Movement Disorder: Possible Relationship with Antiribosomal P Antibodies - Ozcan, Muhammed Emin; Altinoz, Meric Adil; Karadeli, Hasan Huseyin; ASİL, Talip; ASİL, TALIP; Kocer, Abdulkadir (My University, 2013)
Complex movement disorder is a relatively rare presentation of neurolupus. Antiphospholipid antibodies are associated with movement disorders likely via aberrant neuronal stimulation. Antiribosomal P antibodies have been previously associated with neuropsychiatric disorders but their correlation with movement disorder was not previously established. Our case report involves a 17-year-old Caucasian female patient positive for only antiribosomal P antibody and lupus anticoagulant who presented with a sudden onset of complex movement disorder. After complete cessation of physical signs with olanzapine, anticardiolipin and anti-beta 2 glycoprotein I antibodies became positive which indicates a likely discordance between movement disorder and antiphospholipid antibodies. This also indicates a potential causal role of antiribosomal P antibodies in inducing movement disorder.